Peculiar transient behaviors of organic electrochemical transistors governed by ion injection directionality - Kim, Ji Hwan; Halaksa, Roman; Jo, Il Young; Ahn, Hyungju; Gilhooly-Finn, Peter A.; Lee, Inho; Park, Sungjun; Nielsen, Christian B.; Yoon, Myung Han (Nature Communications, 2023)
Despite the growing interest in dynamic behaviors at the frequency domain, there exist very few studies on molecular orientation-dependent transient responses of organic mixed ionic–electronic conductors. In this research, we investigated the effect of ion injection directionality on transient electrochemical transistor behaviors by developing a model mixed conductor system. Two polymers with similar electrical, ionic, and electrochemical characteristics but distinct backbone planarities and molecular orientations were successfully synthesized by varying the co-monomer unit (2,2’-bithiophene or phenylene) in conjunction with a novel 1,4-dithienylphenylene-based monomer. The comprehensive electrochemical analysis suggests that the molecular orientation affects the length of the ion-drift pathway, which is directly correlated with ion mobility, resulting in peculiar OECT transient responses. These results provide the general insight into molecular orientation-dependent ion movement characteristics as well as high-performance device design principles with fine-tuned transient responses.